Alteration of Ovoproducts : From Metabolomics to Online Control - Goncalves, Olivier; Legrand, Jack (ISTE Press, 2018)
"Characterizing the Alteration of Ovoproducts Using New Analytical Approaches focuses on the capabilities (potential or proven) of the latest metabolomics based analytical approaches for the (early) diagnostic of the alteration of ovoproducts during their production/preservation processes. It details the ovoproduct matrix, their known sources of biotic and abiotic alteration, and their associated biomarkers. In addition, the book covers the capabilities (exploratory and characterization) of the latest metabolomics tecnics, both invasive and non-invasive, including chromatography, nuclear magnetic resonance, mass spectrometry, NMR, MS - including FTICR-MS -, and vibrational spectroscopy, such as Infrared - MIR, NIR - or Raman). In final sections, the next generation of online sensors derived from the latest technics is discussed for their applicative potential in industry (NIR, Raman, chromatography, benchmark NMR, and more). Details the matrix of egg products. Explores the latest metabolic techniques. Strengthens the linkages between the agri-food, microbiological and chemical analytical communities"--